(untitled) (NTU Journal of Agriculture and Veterinary Science, 2025)
The experiment was carried out using 20 genotypes obtained from the International Research Center (ICARDA) in addition to a local cultivar available in the local market, where the cultivation process took place in the research centre of the College of science / University of mosul in the spring season 2019-2020 using random complete block (R.C.B.D investigated the following characteristics: number of days until 50% of the plants flower, secondary branches/plant, height of fresh pod in cm, number of pods per plant, number of seeds per pod, harvesting index, 100-grain weight (gm), biological yield gm, and grain yield per plant gm. investigated the following characteristics: number of days until 50% of the plants flower, secondary branches/plant, height of fresh pod in cm, number of pods per plant, number of seeds per pod, harvesting index, 100-grain weight (gm), biological yield gm, and grain yield per plant gm. To evaluate genetic variability, correlations, and direct and indirect impacts between yield and yield components, a study on path analysis, genetic variability, and correlations was conducted. The number of days that plants flower at 50% and the number of main branches in a plant, as well as the secondary branches/plant, pods per plant, and 100-grain weight (gm), were found to have the highest genotypic and phenotypic coefficients of variation. Certain traits, including the number of seeds per pod, biological yield per plant, and harvest index, had a strong phenotypic and genetic link while others, like plant height, the secondary branches/plant, and the height of the first pod, did not approach the significant limit. Analysis of path coefficients (seed yield as a dependent variable) concluded that the number of seeds per plant, biomass yield, biological yield, number of tillers, and number of secondary branches in the plant had all had a beneficial direct impact on seed yield. When choosing the highest-yielding genotypes in chickpeas, it is crucial to consider factors like grain yield and seed weight in the pod where the phenotypic path coefficient was significant for certain traits and in the desired direction.